Conversational Implicature on Voice Character Dialogue in Genshin Impact - Shafira Maya Juliana Putri; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This study aims to determine the functions of the conversational implicature which is the area of pragmatics; the function of the conversational implicature itself in the dialogue in Genshin Impact. Implicature is not only found in movies or fictional novels, yet it exists in several artworks including games. This study uses qualitative descriptive methods to analyse the types of meaning of implicature in pragmatics in the dialogue written in Genshin Impact. The data is taken from the Genshin Impact which is an action role-playing game by mining the conversations using manual data mining. The writer used Grice's theory of conversational implicature, which identifies the issue of utterance interpretation to which Paul Grice sought a solution and works through his ideas on the 'logic' of conversation. The data was collected after observation and analysis while playing the game Genshin Impact. The result shows that there are 5 data that has its own function in the sentence, the function is explained through 2 meanings, there are 11 utterances which is included 3 data in the particularized conversational implicature function, and 6 utterances include in 2 data of generalized conversational implicature. It could be concluded that the game has commonly particular conversational implicature function.